2018
DOI: 10.1111/vox.12704
|View full text |Cite
|
Sign up to set email alerts
|

The effect of red‐blood‐cell transfusion on fatigue in hospitalized patients with anaemia

Abstract: Transfusion during hospitalization is associated with reduced fatigue 30 days postdischarge in patients with higher levels of baseline fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…[9,4,8] Few studies have measured fatigue in patients for more than a few days after transfusion to examine the time-course of fatigue after RBC transfusion. [5,7] In hospitalized adults, Prochaska et al [5] found that transfusion during an inpatient admission was associated with reduced fatigue at 30 days after discharge. In women with postpartum hemorrhage, subjects randomized to receive RBC transfusion reported less fatigue at 4-6 weeks than women who did not receive transfusions, although the difference was not deemed to be clinically important.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[9,4,8] Few studies have measured fatigue in patients for more than a few days after transfusion to examine the time-course of fatigue after RBC transfusion. [5,7] In hospitalized adults, Prochaska et al [5] found that transfusion during an inpatient admission was associated with reduced fatigue at 30 days after discharge. In women with postpartum hemorrhage, subjects randomized to receive RBC transfusion reported less fatigue at 4-6 weeks than women who did not receive transfusions, although the difference was not deemed to be clinically important.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is a well-known symptom of anemia, and low hemoglobin levels are correlated with worse fatigue and poor quality of life in patients with cancer. [1][2][3] Recent studies of hospitalized general medical service patients indicate that red blood cell (RBC) transfusion improves short-term fatigue in inpatients, [4,5] but whether transfusion in the hospital is associated with a sustained, clinically important improvement after hospital discharge is not clear. [6,5,7] Similarly, few studies have examined whether RBC transfusion improves fatigue in outpatient transfusion recipients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a physiological perspective, we found that improvements in Hb soon after a transfusion were accompanied by greater sustained improvement in executive abilities between transfusions, suggesting that normalizing Hb could improve executive abilities for individuals with SCD. Relatedly, lower Hb is associated with fatigue, which is a commonly reported symptom of SCD that can be improved following a transfusion . Further, fatigue is related to poorer parent‐reported executive function in children with SCD .…”
Section: Discussionmentioning
confidence: 99%